PROBLEMATIKA KETERSEDIAAN AIR BAKU DALAM UPAYA PENCAPAIAN TARGET SUSTAINABLE DEVELOPMENT GOALS DI INDONESIA KASUS: DAERAH ALIRAN SUNGAI BATANGHARI WILAYAH SUMATERA BARAT - Setiawan, Arief; Paramita, Hesti Nurita (Jurnal Transformasi Global, 2019)
AbstractThe damage of the Batanghari River Basin (DAS) in West Sumatra has caused the raw water supply in the area to be disrupted. Those damages could have implications for Indonesia's achievements in sustainable development goals (SDGs). Such conditions can also disrupt to the achievement of SDGs globally. This happens because the SDGs are designed in such a way as to adapt the concept of earth system in which each smallest unit in human life can have global implications. In this case, the Government of Indonesia carried out a series of efforts so that the raw water supply from the Batanghari River did not decrease in its debit. Various measures and strategies, both in the form of regulations and development planning, have been prepared in such a way and are considered to be in line with SDGs targets. This article is a collaborative work of two authors with a much different scientific background. This shows that the study of contemporary international relations has a high flexibility in responding global phenomena(s). Keywords: Earth System, Sustainable Development Goals, river basin, raw water